Development of a mathematical cognitive assessment instrument oriented to literacy, numeracy, and local culture - Hariyanto; Sutama; Yulia Maftuhah Hidayati (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
The paradigm of mathematics assessment has shifted from memorization- and procedure-oriented approaches toward an emphasis on reasoning, problem solving, and mathematical representation. This study aimed to develop a valid and reliable numeracy literacy-oriented cognitive assessment instrument for the statistics topic, specifically measures of central tendency. The study employed a Research and Development (R&D) method using the ADDIE model and was conducted at MTs N 2 Brebes during the 2024/2025 academic year, involving 96 students. Data were collected through interviews, questionnaires, and tests and analyzed using descriptive quantitative analysis. The results show that the developed instrument has very high validity, with material expert validation scoring 0.86 and item expert validation scoring 0.87, while content validity reached 0.57, indicating a moderate category. The reliability coefficients were 0.44 for multiple-choice items (moderate) and 0.57 for descriptive items (high). The items demonstrated good psychometric characteristics, with moderate to high difficulty levels and adequate discrimination power. In terms of practicality, the instrument was rated very practical by five teachers (average score 88.67) and 66 students (average score 83.6), indicating that it is easy to use and well understood. Overall, the findings indicate that the developed assessment instrument is valid, reliable, and practical for wider implementation and contributes to the development of mathematics assessment aligned with contemporary learning paradigms that emphasize numeracy literacy at the secondary school level.